Institutional crisis and new ways to interact on social media: A comparative study of political participation by México and Ecuador’s youth (2018)
The Latin American communication media crisis, visible from a dramatic drop in advertising financing and a progressive move by audiences toward new media, is linked to the public institution crisis. This communication media crisis denotes the emergence of social practices focused on user activation, thereby causing a decline in vertical mediation and a detriment to new routines which, according to collective intelligence, tend to develop collaborative symbolic environments and a general greater empathy. These phenomena do not extend beyond Latin America in a horizontal or global way. México and Ecuador are two countries that are representative of Latin America’s trends. México, on one hand, is a context with high media concentration and powerful communicational groups whose links result from the heavy bipartisanship that has ruled this country over the last three decades. Ecuador, on the other hand, is a context where former President Rafael Correa’s administration (2007–2017) created a new legal framework that favors—at least from a normative point of view—better democratization of communication media through the implementation of institutions that are tasked with ensuring diversity in media and encouraging citizen involvement in co-government tasks. This research compares the results from surveys administered to more than two thousand college students from México and Ecuador, in which these two strategic groups were asked about their views on phenomena such as online and offline political participation and information consumption in order to find out if there any differences between México and Ecuador’s concept of political participation among young college students. © Common Ground Research Networks, Daniel Javier de la Garza Montemayor, Daniel Barredo Ibáñez, Abraham A. Hernández Paz, Some Rights Reserved,